Self-management of multiple chronic conditions among African American women with asthma: A qualitative study - Janevic, Mary R. (J Asthma, 2013)
OBJECTIVE: African American women are disproportionately burdened by asthma morbidity and mortality, and may be more likely than asthma patients in general to have comorbid health conditions. This study sought to identify the self-management challenges faced by African American women with asthma and comorbidities, how they prioritize their conditions, and behaviors perceived as beneficial across conditions. METHODS: In-depth interviews were conducted with 25 African-American women (mean age 52 years) with persistent asthma and at least one of the following: diabetes, heart disease, or arthritis. Information was elicited on women’s experiences managing asthma and concurrent health conditions. The constant-comparison analytic method was used to develop and apply a coding scheme to interview transcripts. Key themes and subthemes were identified. RESULTS: Participants reported an average of 5.7 comorbidities. Fewer than half of the sample considered asthma their main health problem; these perceptions were influenced by beliefs about the relative controllability, predictability, and severity of their health conditions. Participants reported ways in which comorbidities affected asthma management, including that asthma sometimes took a ‘backseat’ to conditions considered more troublesome or worrisome. Mood problems, sometimes attributed to pain or functional limitations resulting from comorbidities, reduced motivation for self-management. Women described how asthma affected comorbidity management; e.g., by impeding recommended exercise. Some self-management recommendations, such as physical activity and weight control, were seen as beneficial across conditions. CONCLUSIONS: Multiple chronic conditions that include asthma may interact to complicate self-management of each condition. Additional clinical attention and self-management support may help reduce multimorbidity-related challenges.